Anion‐Coordination‐Induced Turn‐On Fluorescence of an Oligourea‐Functionalized Tetraphenylethene in a Wide Concentration Range1. (18th May 2014) - Zhao, Jie; Yang, Dong; Zhao, Yanxia; Yang, Xiao‐Juan; Wang, Yao‐Yu; Wu, Biao
Abstract A tetrakis(bisurea)‐decorated tetraphenylethene (TPE) ligand (L2) was designed, which, upon coordination with phosphate ions, displays fluorescence "turn‐on" over a wide concentration range, from dilute to concentrated solutions and to the solid state. The fluorescence enhancement can be attributed to the restriction of the intramolecular rotation of TPE by anion coordination. The crystal structure of the A4L2 (A=anion) complex of L2 with monohydrogen phosphate provides direct evidence for the coordination mode of the anion. This "anion‐coordination‐induced emission" (ACIE) is another approach for fluorescence turn‐on in addition to aggregation‐induced emission (AIE).